Relationship of IL-6 and IL-8 levels with tubal ectopic pregnancy - Kadhim, Huda; Khazaali, Enas Adnan Abdulrasol Al (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The frequency of ectopic pregnancy (EP) has increased worldwide during the last 30 years, particularly in underdeveloped countries with low early diagnostic rates. Ectopic pregnancy is the major cause of first-trimester deaths. Interleukins are immunomodulatory cytokines that modulate inflammatory responses and help humans conceive. Aim of the study was to evaluate the predictive value of interleukin-6 and interleukin-8 in tubal ectopic pregnancy. Methods: This case control research was undertaken in the Department of Obstetrics and Gynaecology at Al-Emamein Al-Kadhemein Medical City/Baghdad from January 1, 2022 to January 1, 2023. The study analysed 30 patients with missed cycles, positive β-HCG tests, vaginal bleeding, and ruptured tubal ectopic pregnancy diagnosed via transvaginal ultrasound (group A) and 30 patients with intrauterine missed miscarriage (group B). The control group (group C) included 30 ladies with uncomplicated intrauterine pregnancies of matched gestational age. Results: Interleukin-6 was substantially greater in ectopic pregnancy than miscarriage and normal intrauterine pregnancy. Ectopic pregnancy and miscarriage had higher levels of interleukin-8 than normal intrauterine pregnancy, but there was no difference. Interleukin-6 levels ≥76.1 pg/ml were linked to 90% sensitivity and 85% specificity in predicting ectopic pregnancy. Interleukin-8 was neither sensitive nor specific for ectopic pregnancy. Conclusions: Measurement of IL-6 may have a predictive value in cases of ruptured tubal ectopic pregnancy. IL-8 was a poor predictor for ectopic pregnancy.